DC-CTL targeting carbonic anhydrase IX gene combined with iAPA therapy in the treatment of renal cell carcinoma - Heran Ma; Yi Tan; Dingke Wen; Na Qu; Qunfang Kong; Kun Li; Suxia Ma; Jianhui Zhang (Taylor & Francis Group, 2021)
Introduction To deliver specific antigens in tumor immunotherapy, tumor cell lysates are commonly used to sensitize dendritic cells (DCs). However, the lysates possess low immunogenicity and contain many types of non-tumor-related antigens, which may induce autoimmune diseases. Tumor antigen peptides can provide high specificity but are expensive and their short half-lives limit their clinical application. Methods In this study, we used adenovirus to transfer the carbonic anhydrase IX (CA9) gene into DCs to generate specificity to renal cell carcinoma (RCC) which is the most common space-occupying lesion in humans. Inhibition of antigen presentation attenuators (iAPA) technology was also used to enhance the DC delivery capacity. Finally, DCs were co-cultured with cytotoxic T-lymphocytes (CTLs) and the anti-tumor effects were evaluated. Results The results showed that the CA9-DC-CTLs possessed a high specificity to CA9-positive cells and showed stronger anti-tumor activity than GFP-DC-CTLs both in vitro and in vivo. Discussion These findings may suggest a novel treatment option for RCC.